Scientific evidence and public policy: a systematic review of barriers and enablers for evidence-informed decision-making - Suazo-Galdames, Iván Claudio; Saracostti, Mahia; Chaple-Gil, Alain Manuel (Frontiers in Communication, 2025)
IntroductionThis systematic review synthesizes empirical research on the integration of scientific evidence into public policy formulation across diverse governance contexts. While global support for evidence-informed policymaking is increasing, persistent institutional barriers, political resistance, and limited science-policy interaction continue to constrain the effective use of research in decision-making.MethodsGuided by the PRISMA 2020 framework, the review identified 119 peer-reviewed articles from Scopus and Web of Science databases. Eligible studies included empirical analyses on the mobilization, translation, and institutionalization of scientific knowledge in policy processes. A thematic synthesis was conducted, classifying studies into six categories: science-policy participation, institutional capacity, political dynamics, trust and legitimacy, political support, and international collaboration.ResultsMajor barriers included fragmented advisory systems, limited data infrastructures, and weak communication between researchers and policymakers. Key enabling factors comprised dedicated scientific advisory bodies, knowledge brokerage mechanisms, international cooperation, and co-production of knowledge. Most studies focused on the health policy sector, with a geographic concentration in high-income countries such as the United Kingdom, the United States, and Canada.DiscussionFindings highlight the urgent need to institutionalize scientific evidence in policy formulation through formal governance frameworks, sustained stakeholder engagement, and robust science-policy interfaces. Advancing transparent, inclusive, and evidence-based governance will require cross-sector collaboration, epistemic trust, and political leadership committed to bridging the gap between research and public policy.